Features of construction of the traction electric drives movable electrical systems - Кулагін, Дмитро Олександрович; Чернецький, Богдан Сергійович (Technology audit and production reserves, 2015)
The features of construction of systems of traction electric drives for various types and designs of mobile electrical systems. The analysis of practical experience in building systems of traction electric drives and synthesis methods for determining the structure and parameters under the given requirements from the side of the movable electrical complex. Study of construction of systems of traction drives with different types of engines are relevant from the point of view of achieving the maximum level of energy savings through the implementation of all these requirements. Means of improving energy efficiency and productivity of mobile electrical systems in difficult situation on the market of energy resources allow for greater independence of the domestic transportation industry from a number of economic and political factors that have a significant impact on the basic indicators of work of many enterprises and the budget of private vehicle owners and provide optimal design and more efficient operation in various sectors of the economy. In the result of the analysis has been further development of the method for determining the structure and parameters of traction electric drives of rolling electrical complex by taking into account the specific requirements of the Executive mechanism, whereby the analytical requirements for different groups of mobile complexes on details of construction of the traction electric drives, choice of motor traction drives based on the distribution of energy flows on traction needs and providing for their own needs, which allows to determine the optimal structure of such traction drives. In particular, the analysis of practical experience of building traction systems and generalization of methods of determining the type and parameters of traction motors under the given requirements from the side of the movable electrical complex, which allows for precise selection of the type and parameters of the traction electric drive.